Foam-like GaN: Study on the controlled tuning of pore size by R group change in amino acid etchant and its ultra-high photocurrent response. (February 2022) - Zhang, Zi'ang; Zhang, Long; Liu, Zeng; Li, Kaikai; Nie, Lifan; Zhou, Quan; Dong, Zhaobo; Liu, Qingyi; Yang, Limei; Zhang, Shaohui; Pan, Gebo
Abstract: Relative to ionic liquids, in addition to mild physical and chemical properties, and are environmentally friendly, amino acids possess a smaller molecular weight as well. Herein, we developed a foamed GaN (F-GaN) nanostructures with uniform appearance and smooth pore wall, which prepared by the photoelectrochemical etching (PECE) in amino acid etchant. The controlled adjustment of the average pore size from 27.33 nm to 56.41 nm was achieved by the change of R group, verifying the amino acids with different molecular weight can effectively adjust the pore size of the F-GaN. In addition, the highest pore density was estimated to 1.34 × 10 11  cm −1, which reached a peak value in the field of GaN wet etching ever before. Importantly, the highest photocurrent of the as-obtained F-GaN was 21 times than the planar GaN, which demonstrated F-GaN nanostructures had great potential in the photoelectric and optical devices. Highlights: F-GaN was prepared by PECE in amino acid etchant. The controlled adjustment of the average pore size was achieved by the change of R group. The highest photocurrent of the F-GaN was 21 times than the planar GaN.